Image of College Student Movement Organization After Reformation of Indonesia - Fuad .; Nuriyatul Lailiyah, S.Sos, M.I.Kom (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
College Student Movement Organization of Indonesia is inseperable part from politic reformation of Indonesia. “Agent of Change” is the appropriate word to describe them. However, after politic reformation of Indonesia, college student movement as if experience derivation of image among college students. Viewed from reduction of college students participation to join college student movement organization.This study aims to understand and comprehend about image of college student movement organization, using qualitative and quantitative (mix method). The concepts which used by this study are related with image of stakeholder and public relation. The study found image of college student movement organization after reformation of Indonesia politic.The findings were compiled in a few points: 1) Positive image of college student movement organization viewed as popular, have good personality, closer, have qualified qadres and loyal to intra campus organization in intra campus’s organizational. Then, have qualified leadership, have good academic capability, improtant for Indonesia, innovative, have good contribution for Indonesia’s future, attractive to follow, have competence and talented cadres in intra campus’s organizational, have good communication with stakeholder, be responsible to their activity. 2) Negative image of colege student movement organization viewed as unpopular in common college students’s perspective, not closer with common college students, key stakeholders have compound perspective in cadre’s personality, key stakeholders have compound perspective in cadre’s loyality for intra campus organizational, have not loyal perspective to Indonesian people’s impotance, inra campus organizationals have less competence perspective about college student movement board’s management, key stakeholders have compound perspective for cadre’s qulified, intra campus organizationals have less good perspective about transparence about fund source and management. All negative images of college student movement organization relate to stakeholder reaction are on disappointment and surprise level with trust damaged on trust questioned (which may recover rapidly)and trust dented (which recover by good public relationship). The effort to restore stakeholder trust are with openness and expose related to gaits, activities, and values which embraced bu college student movement organization to stakeholder. Then do some internal revamping for college student movement organization cadres related to first oriented cultivation and values of organization.